Linking Decent Work and Well-Being Among Chinese Millennial Employees: A Psychology of Working Perspective - Wan, Wei; Cao, Tingting (Frontiers in Psychology, 2022)
Drawing from the psychology of working theory, this study aims to understand how decent work is related to employee well-being. Specifically, it explored the role of need satisfaction (i.e., survival, social contribution, and self-determination) in the relationship between decent work and employee well-being, and compared the mediating effects of the three types of need satisfaction. After collecting a sample of 421 millennial employees in China through online questionnaires, the study conducted the analysis of the data and found that decent work positively predicted well-being of millennial employees. While social contribution need satisfaction and self-determination need satisfaction partially mediated the effect of decent work on well-being of millennial employees, the mediating effect of survival need satisfaction was not significant. Compared with social contribution need satisfaction, self-determination need satisfaction had a more significant mediating effect on well-being of millennial employees. The study does extend the literature on the antecedents of employee well-being and the results can offer some implications for managers to enhance well-being of millennial employees.